Society «Educational community named after Mykhailo Drahomanov in the Wetzlar Ukrainian POW camp, Germany, 1917 - early 1918) (based on the materials of the «Hromadska Dumka») - Sribnyak, Ihor (Educological discourse, 2023)
The article analyzes the peculiarities of the activity of the «Educational Community named after Mykhailo Drahomanov» in the camp of Ukrainian prisoners of war in Wetzlar (Germany), which during 1917 achieved the greatest achievements in its activities, which was due to the general intensification of national organizational work in the Wetzlar camp after the overthrow of the Russian tsar. In their work, the enlightened people focused on two main categories - the illiterate, for whose services the People's School worked, and at the same time those who already had a certain educational qualification (including graduates of the mentioned school), who had all the opportunities to replenish the baggage of their knowledge. A notable feature of the current work of Ukrainian activists was the involvement of prisoners in political presentations, which prepared a significant number of camp inmates to accept the idea of creating an independent Ukrainian state. The credit for this belonged primarily to educators from among Galicians, who at the call of the IDF worked in the camps and managed to raise a whole cohort of Ukrainian patriots among the prisoners, who continued the work of their teachers, giving lectures in separate barracks (by conducting readings of abstracts and impromptu evenings), as well as and outside the camp (during the dispatch of prisoners to work as part of work teams). One of the significant results of this work was the formation of a distinctly national worldview in the majority of the prisoners of this camp, which made it possible for them to further join the ranks of the armed forces of the Ukrainian People's Republic, which, starting from the moment of the Bolshevik coup, stood up to protect Ukraine from aggressive encroachments by Moscow.